2015
DOI: 10.1371/journal.pone.0139233
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosomal miRNAs in Persons with and without Alzheimer Disease: Altered Expression and Prospects for Biomarkers

Abstract: To assess the value of exosomal miRNAs as biomarkers for Alzheimer disease (AD), the expression of microRNAs was measured in a plasma fraction enriched in exosomes by differential centrifugation, using Illumina deep sequencing. Samples from 35 persons with a clinical diagnosis of AD dementia were compared to 35 age and sex matched controls. Although these samples contained less than 0.1 microgram of total RNA, deep sequencing gave reliable and informative results. Twenty miRNAs showed significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
265
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(277 citation statements)
references
References 45 publications
12
265
0
Order By: Relevance
“…Pathological proteins or miRNAs in exosomes have emerged as potential biomarkers for AD and other neurodegenerative diseases [34, 51, 52]. A recent study demonstrated the presence of Tau in exosomes isolated from blood of patients with AD or frontotemporal dementia (FTD) and that the exosomal levels of total Tau and Tau phosphorylated at T181 or S396 for AD and FTD were significantly higher than in control subjects [51].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological proteins or miRNAs in exosomes have emerged as potential biomarkers for AD and other neurodegenerative diseases [34, 51, 52]. A recent study demonstrated the presence of Tau in exosomes isolated from blood of patients with AD or frontotemporal dementia (FTD) and that the exosomal levels of total Tau and Tau phosphorylated at T181 or S396 for AD and FTD were significantly higher than in control subjects [51].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Lugli et al used Illumina deep sequencing to determine differential expressions of miRNAs in plasma from patients with AD and healthy control subjects [89]. They found a total of 20 miRNAs downregulated; four miRNAs (miR-548at-5p, miR-138-5p, miR-5001-3p, and miR-659-5p) upregulated; and seven miRNAs (miR-185-5p, miR-342-3p, miR-141-3p, miR-342-5p, miR-23b-3p, miR-338-3p, and miR-3613-3p) significantly downregulated in AD patients compared to controls (Table-1).…”
Section: Circulatory Mirnas In Alzheimer’s Diseasementioning
confidence: 99%
“…The following patients were excluded from the study: patients receiving heparin therapy at the time of the blood draws (since heparin can interfere with RNA isolation); patients who had been diagnosed with any nonAlzheimer's type of dementia; and patients suffering from other diseases, such as AMI, cancer, Parkinson's disease, and multiple sclerosis, as these diseases can cause differences in miRNA expression (Lugli et al 2015). …”
Section: Study Populationsmentioning
confidence: 99%